Presence of a Halophila baillonii Asch. (Hydrocharitaceae) Seagrass Meadow and Associated Macrofauna on the Pacific Coast of Costa Rica - Samper Villarreal, Jimena (2014)
Seagrasses in the eastern Pacific are mainly confined to temperate and subtropical regions of North America, with limited reports of presence in Central America and Chile. We report a unique monospecific meadow of Halophila baillonii for the Eastern Tropical Pacific in Golfo Dulce, southern Pacific coast of Costa Rica. This report constitutes the first sighting of seagrasses from the Pacific coast of Costa Rica since disappearance of the only reported seagrass meadow, of Ruppia maritima and Halophila baillonii, in 1996. Twenty sediment cores (5 cm diam., 15 cm deep) were taken at 10 locations for characterization of seagrass and associated macrofauna, grain size distribution, and carbonate analysis. Area of the seagrass meadow was 884 m-2, foliar shoot density was 4,841 ± 3,433 shoots m-2, and biomass was 30.7 ± 16.3 g DW m-2. Invertebrate fauna were mainly infaunal, dominated by polychaetes. Seven invertebrate species are new records for Costa Rica and 13 for Golfo Dulce. Further research is needed to elucidate dynamics and ecological drivers of seagrasses in the Eastern Tropical Pacific.